Assessment of Anxiety in Long-Term Care Residents: Issues and Strategies. (October 2021) - Pifer, Marissa A.; Segal, Daniel L.; Jester, Dylan J.; Molinari, Victor
The experience of clinically significant anxiety and anxiety disorders represent significant and often debilitating problems for many residents in long-term care (LTC) settings. However, anxiety problems often go undetected and untreated in this growing population. The purposes of this paper are to examine the prevalence and impact of anxiety problems among residents in LTC facilities, describe the efficacy of the current instruments that are used to detect anxiety in these settings, and provide clinical guidance for the thorough assessment of anxiety. Regarding measurement tools, the GAI, GAI-SF, GAS-LTC, and the BADS are the only self-report measures designed for older adults that have been successfully validated for use with older adults living in LTC settings. Clinicians should focus on ways to educate LTC directors and staff to emphasize the importance of screening and assessing for anxiety, using validated measures, to improve the assessment and treatment of anxiety in their residents.